HUBUNGAN PERSONAL HYGIENE DENGAN MASALAH KEPUTIHAN PADA IBU PEMULUNG DI TPA TADUKAN RAGA STM HILIR - Astriana Fransiska Butarbutar; Juli Fransiska Tumanggor (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
Whitish (flour albus) is a condition of the vagina when removing fluid or mucus that resembles pus. Leucorrhoea is not always a disease because there is also normal vaginal discharge. Poor personal hygiene cause vaginal discharge. The purpose of this study was to determine the relationship between personal hygiene and vaginal discharge problems in scavenger mothers in the Landfills Tadukan Raga STM Hilir 2018. The type of research used was descriptive research with a cross sectional approach, namely an analytical survey. The sample of this study amounted to 23 respondents using total sampling. The data analysis was carried out by univariate and bivariate with Chi Square statistic test with a significance limit (Î±) of 0,05. The reseach showed that the majority of scavenger mothers had good skin hygiene, and good hand and nail hygiene as many as 13 people with a percentage (56,5 %), and having poor Genetalia Hygiene as many as 13 people with a percentage (56,5%). The conclusion there is no relationship between skin hygiene and vaginal discharge (Ï = 0,341), there is no relationship between hand and nail hygiene with vaginal discharge (Ï = 0,660), and there is a correlation between genetalia hygiene and vaginal discharge in scavenger mothers (Ï = 0,019). Skin hygiene, hand and nail hygiene are not entirely a factor causing vaginal discharge problems, there are still many other causal factors which are the limitations of this study, while genetalia hygiene greatly affects the occurrence of vaginal discharge problems. Keywords: whitish, Personal hygiene, scavenger mothers